Overview of Methods of Biometric Based Key Protection - Khachatrian, Gurgen; Malkhasyan, Narek (Mathematical Problems of Computer Science, 2021)
The security of any modern cryptosystem relies on the assumption that secret keys used for the system such as secret keys for message encryption and authentication as well as private keys of public key cryptosystem are unknown. This assumption is not easy to satisfy in most practical applications. The most widely applicable method uses conventional passwords to encrypt secure keys stored on the computer device. However passwords are vulnerable against many kinds of attacks since they can be either guessed or stolen. Another basic problem is the user authentication. It is well known that when using a traditional and widely used cryptographic methods the user authentication is achieved by challenge -response protocols, the essence of which consists in verifying that the party which wants to confirm his authentication possesses a secret key. In this paper an overview of methods of password generation from biometric data is presented along with the discussion of the remaining challenges and possible directions of future research.